STRATEGIC PLANNING OF REVERSE LOGISTICS SYSTEM AMONG OMNICHANNEL COMPANIES: A QUALITATIVE STUDY (Journal of Technology and Operations Management, 2021)
In an omnichannel context, reverse logistics systems are hazy and difficult to manage. Improper reverse logistics management can lead to consumer unhappiness and increased costs for omnichannel companies. Therefore, the understanding of reverse logistics in omnichannel environment is important to improve the management of reverse flow. This paper aims to explore the factors in reverse logistics system that would improve omnichannel firm performance. The semi-structured interviews were arranged and useful to obtain comprehensive understanding about reverse logistics system among companies in the omnichannel environment. Thematic content analysis was conducted to analysis the interview. The thematic analysis has provided a thorough understanding of reverse logistics in omnichannel companies, as well as their role in improving firm performance. Overall, there are nine major themes identified which was top management support, formalization, flexibility, information system, collaboration, supplier, customer, regulator, and competitor. The themes identified from omnichannel companies can be categorized into two categories which were firm and task environment factors. Omnichannel companies were reported a positive attitude in these reverse logistics factors to support the improved firm performance. The themes discussed because were thought to help in managing reverse logistics system and thus ensure the company's success. The findings of this study also providing a robust structural for understanding in omnichannel reverse logistics system.In conclusion, managers and related practitioners could manipulate the reverse logistics systems to improve firm performance. At the same time, the outcome would provide more comprehensive understanding in the strategic criteria of reverse logistics management.